Travel Agent Students' English Reading Materials: Students' Perspective - Sinta Octaviana; Eryansyah Eryansyah; Rita Inderawati (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
The study aims to study travel agent students' perception and needs toward English reading materials used in English learning at Vocational High School. Two sets of questionnaires were used to collect the data of the study. The first set of the questionnaire was used to find out students' perceptions, and the other one was used to analyze the needs of the students. The needs analysis was done based on four aspects of needs assessment: TSA, PSA, Deficiency Analysis, and Strategy Analysis. Afterwards, the obtained data were analyzed quantitatively. The results indicated that the students viewed English as an essential subject to learn. Furthermore, the students also perceived that integrating technology and Palembang culture into the English reading materials (textbook) was important in this 21st-century era. Besides, the students also believed that the current materials learned at school were not yet suitable for their needs, and they currently had difficulties learning English. In addition, the students hoped the reading materials contained the 21st-century skills and their local cultures related to their major. Based on the needs analysis results, further steps were necessary to provide the English reading materials integrated to Palembang local culture, which could facilitate students to improve their English proficiency in line with their department and the demands of the 21st century.